A Narrative Enquiry into Gender Role Differentiation by Males of the Family in Career Choice Decisions of Female Child. Issue 2 (July 2019) - Tiwari, Himanshi
Abstract: Choosing a career is a crucial and significant milestone in one's life. It becomes even more critical when a woman makes her career choice decisions. Women have a strong case to be free to choose the career of their choice, and contribute in the economic and social well-being of not only their own but of the society on broader grounds, to the fullest of their capabilities. This article makes an attempt to highlight gender role differentiation in the career choice decisions of women. The article follows an autobiographical approach to career counseling and aims to highlight the life story of 25 girls who are pursuing their management graduation in the national capital region of India. "Narrative enquiry method" is used to understand how respondents/participants/interviewees build meaning from within their system of belief, attitude, values, and concepts that outline judgment of individuality and self-identity. Gender role differentiation is found as an influence and barrier in the phenomena of selection of a field of study and even specialization. The findings of this article can be used in crafting programs for providing career counseling and guidance to female management graduates.